ZEMSKY ADULT EDUCATION IN THE MODERNIZATION PROCESS IN THE STAVROPOL REGION IN 1913-1916 - T. E. Pokotilova (Гуманитарные и юридические исследования)
Until recently, historical science, especially its foreign representatives, virtually denied that pre-revolutionary Russia underwent stock modernization, pointing out the lack of a number of inherent classical modernization components in the socio-economic transformations in the country's history. The given material on the history of activities of the Stavropol elective district council on the organization of adult education in 1913-1916, on the contrary, gives examples of significant structural, cultural and mental changes in the Russian Empire in the early XX-th century, which are classified as modernization changes.